Geographic distribution of the land snail family Spiraxidae (Gastropoda: Pulmonata) in Mexico - Maldonado-Sánchez, César Fabricio (2022)
Introduction: Spiraxidae is the most diverse family of terrestrial gastropods in Mexico with a mainly neotropical distribution. However, the influence of environmental conditions in this region on its distribution is still poorly known. Objective: To determine zoogeographic affinities and the influence of environmental factors on the distribution of Spiraxidae in Mexico. Methods: We compiled museum distribution records and used models to establish areas with similar species composition, species concentration, affinities and relationship with environmental variables. Results: We found 231 species and subspecies, 96 in Veracruz state and 74 in Sierra Madre Oriental. The main zoogeographic affinity was neotropical. Mountain mesophyll forest had the most species and subspecies (93). Three of zone groups have a particular species composition and 67 % of the species are habitat specialists. Species presence follows an environmental gradient, with broadleaf evergreen tree cover and average annual precipitation as determining variables. Northern species had greater tolerance to aridity and reduced leaf cover. Conclusions: Spiraxidae has its greatest diversity in the Southern states of Mexico; however, the Northeastern zone has more species records. These snails mostly occur in mesophyll mountain forest and tropical evergreen forest. Species from Northern Mexico had greater tolerance to sites with low rainfall and less broadleaf evergreen tree cover than Southern species.   Key words: Zoogeography; species richness; MaxEnt, multivariate analysis; spatial segregation